Reliability and validity of the Finnish version of the American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form, patient self-report section - Piitulainen, Kirsi; Paloneva, Juha; Ylinen, Jari; Kautiainen, Hannu; Häkkinen, Arja (BMC musculoskeletal disorders, 2014)
Background The American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES) is one of the most widely used shoulder outcome tools in clinical work and in scientific studies. However, it has not been validated in the Finnish language. The aims of this study were to cross-culturally adapt the ASES to the Finnish language and to study the psychometric properties of the self-report section of the ASES. Methods A total of 105 patients with shoulder symptoms answered the questionnaires of the ASES, a single disability question, the Simple Shoulder Test (SST), and the Short-Form 36 Health Survey (SF-36). The reliability of the ASES questionnaire was studied using a test-retest procedure at 2-week intervals. Psychometric assessment was performed by testing the construct validity, internal consistency, the criterion validity, and the convergent validity of the ASES. Results The reproducibility and internal consistency of the ASES were 0.83 (95% CI 0.70 to 0.90) and 0.88 (95% Cl 0.84 to 0.91). There were no significant differences between the diagnostic groups in the pain scores from the ASES, and the function score was significantly higher in the instability group compared to the other groups. The convergent validity of the ASES correlated with the SST, r = 0.73 (p < 0.001); the single disability question, r = -0.74 (p < 0.001); and the Physical Component Score of the SF-36, r = 0.57 (p < 0.001). Conclusions The Finnish version of the ASES proved to be a reliable and valid tool for assessing shoulder disabilities in patients with different shoulder diagnoses, including rotator cuff disease, instability, and osteoarthritis.